Optimization of Transportation Cost Using Genetic Algorithm - Rizky Kusumawardani (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
Transportation model is application of linear programming that is used to obtain optimum results from distribution issue, especially for minimize transportation cost. General transportation model requires two stages to obtain optimum results such as initial solution method and optimum solution method. These methods are not effective, because it need two stages. Moreover, selection of initial solution method will distinguish the number of iteration on optimum solution method. Therefore, in this study other method such as genetic algorithm that required one stage was used. Genetic algorithm was chosen as alternative method for transportation issue because this method didn’t need two stages and proved to be nice to solve optimization problems. The goal of this study to got method that more effective between combination of North West Corner (NWC) and Modified Distribution Method (MODI) with genetic algorithm to solved two data transportation issues. Based on results, the combination NWC and MODI was more effective for minimize transportation cost than genetic algorithm for two data that solved in this study